Revisiting New Global Governance in Capture Fishery - Dinna Prapto Raharja (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2022)
COVID-19 suffers fishers all over the world, including those in Indonesia. While the pandemic triggered the state to provide relief for fishers, initial interviews and media tracing suggests that in Indonesia, the world’s second largest producer of capture fish, the reaction is not enthusiastic. This paper explores the possible factors behind such reaction, taking the focus on how existing new global governance affected the perspectives of fishers. This paper explores the dimensions of governance that link the perspectives of problem solving at the global level and the way fishers operate. Through in-depth interviews of state apparatus and fishers, also tracing past studies of governance, the paper noted problems that current global governance offered to solve and describe the layers of convergence on “common problems” but not necessarily on “specific problems” that stakeholders try to solve nationally, locally or operationally under the umbrella of global governance. Bringing in the wicked problem discourse, this paper humbly suggests “bringing back embedded liberalism” as inseparable part of new global governance for the sector.